¿Por qué jugar? Sport socialization among Hispanic/Latina female NCAA division I student-athletes - Darvin, Lindsey; Cintron, Alicia; Hancock, Meg (Journal of Amateur Sport, 2017)
Representation of Hispanics/Latinas in intercollegiate athletics is lacking. During the 2014-2015 National Collegiate Athletic Association (NCAA) athletic season, only 2.2 percent of all female Division I student-athlete’s identified as Hispanic or Latina (NCAA, 2015). This low percentage of Hispanic/Latina female participants calls into question how these young women become involved in athletics and sustain their involvement within sport. While previous research has examined the socialization processes of youth athletes and parents of youth athlete participants, there is little research aimed at examining these processes for elite-level athlete participants (Dorsch, Smith, & McDonough, 2015; Greendorfer, Blinde, & Pellegrini, 1986;). Thus, the aim of this current study was to examine the potential factors that may have contributed to consistent sport participation for an elite group of Hispanic/Latina female athletes throughout their youth and collegiate careers. Participants for this study identified as current NCAA Division I Hispanic/Latina female student-athletes. Results showed that family, specifically parents and siblings, contributed to socializing Hispanic/Latina athletes into sport, while family and coaches contributed to the persistence of their athletic endeavors. Findings also show a sense of cultural indifference, youth coaches who invested in the participants long-term, and a significant involvement of the patriarch of the family in their athletic success.